Gender difference in association between H-type hypertension and subcortical ischemic vascular disease - Wang, Juan; Xi, Yuan-Xue; Li, Jia-Qi; Zhu, Wei-Wen (Frontiers in Aging Neuroscience, 2022)
Background: Subcortical ischemic vascular disease (SIVD) is a leading cause of vascular dementia. The present study tries to explore not only the gender-specific association between H-type hypertension and SIVD but also the indirect effects of H-type hypertension on cognition through the ischemic brain injury caused by SIVD. Methods: A total of 601 SIVD patients were included, comprising 322 males and 279 females. H-type hypertension was defined as hypertension accompanied with elevated serum total homocysteine (tHcy) level. The imaging manifestations of ischemic brain injury caused by SIVD were also evaluated, including white matter lesions (WML), lacunar infarction (LI) and brain atrophy (BA). Gender-specific subgroup analyses in association between H-type hypertension and SIVD were conducted, followed by a structural equation model based evaluation of the gender-specific mediating effects of SIVD on the relationship between H-type hypertension and cognition. Results: For males, there was no noticeable difference in WML, LI and BA scores among control group, isolated hypertension group, isolated high tHcy group, and H-type hypertension group in most brain regions, but significant difference was found in all brain regions for females. Multiple regression analyses showed that H-type hypertension was significantly associated with WML, LI and BA for females, but not for males. For males, H-type hypertension mainly affected cognition through direct effect, while the H-type hypertension effect was mediated by ischemic brain injury caused by SIVD for females. Conclusions: H-type hypertension was more closely related to SIVD for females than males, suggesting a gender-specific difference in association patterns between H-type hypertension and cognition.